Abdominal Wall Closure in Elective Midline Laparotomy: The Current Recommendations - Fortelny, René H. (Frontiers in Surgery, 2018)
Introduction The risk of developing an incisional hernia after primary elective median laparotomy is reported in the literature as being between 5 and 20 percent. The goal of this systematic review was to evaluate different closure techniques for midline laparotomies and the use of additional prophylactic mesh augmentation for midline closure in high risk patients. Method A systematic literature search was performed until September 2017. The quality of the RCTs was evaluated and analysed. The data are reported in accordance with the Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Results In the systematic review for closure techniques a total of 23 RCTs and 9 RCTs for the use of prophylactic mesh were included. In elective midline closure the use of a slowly absorbable suture material for continuous closure using the small bites technique results in significantly less incisional hernias than a large bites technique (OR 0.41; 95% CI 0.19, 0.86). The use of prophylactic mesh versus the suture closure of the midline achieved a significant reduction of the incisional hernia rate (OR 0.14 (95% CI 0.07–0.27). Conclusions Based on the currently evidence in midline closure after elective laparotomy in the small bites technique can be recommended to reduce significantly the rate of incisional hernia. The additional use of a prophylactic mesh in high risk patients can significantly reduce the occurrence of incisional hernia.